To simplify the expression \( 2(3v + 9) - 14 - 6(-5v - 4) \), we will follow the order of operations.
-
Distribute the \( 2 \) in the first term: \[ 2(3v + 9) = 6v + 18 \]
-
Distribute the \( -6 \) in the third term: \[ -6(-5v - 4) = 30v + 24 \]
-
Now we substitute back into the expression: \[ 6v + 18 - 14 + 30v + 24 \]
-
Combine the like terms:
- For the \( v \) terms: \[ 6v + 30v = 36v \]
- For the constant terms: \[ 18 - 14 + 24 = 28 \]
Putting it all together, we get: \[ 36v + 28 \]
So, the simplified expression is \( \boxed{36v + 28} \).